The Critical Role of Dust on the [O iii] Planetary Nebula Luminosity Function’s Bright-end Cutoff - George H. Jacoby; Robin Ciardullo (The Astrophysical Journal)
We examine the relationship between circumnebular extinction and core mass for sets of [O iii ]-bright planetary nebulae (PNe) in the Large Magellanic Cloud and M31. We confirm that for PNe within 1 magnitude of the planetary nebula luminosity function’s (PNLF’s) bright-end cutoff magnitude ( M ^* ), higher core-mass PNe are disproportionally affected by greater circumnebular extinction. We show that this result can explain why the PNLF cutoff is so insensitive to population age. In younger populations, the higher-mass, higher-luminosity cores experience greater circumnebular extinction from the dust created by their asymptotic giant branch (AGB) progenitors compared to the lower-mass cores. We further show that when our core-mass–nebular extinction law is combined with post-AGB stellar evolutionary models, the result is a large range of population ages where the brightest PNe all have nearly identical [O iii ] luminosities. Finally, we note that while there is some uncertainty about whether the oldest stellar populations can produce PNe as bright as M ^* , this issue is resolved if the initial–final mass relation (IFMR) for the lowest-mass stars results in slightly more massive cores, as observed in some clusters. Alternatively, introducing a small amount of intrinsic scatter (0.022 M _⊙ ) into the IFMR also addresses this uncertainty.